2023
DOI: 10.1111/dom.15087
|View full text |Cite
|
Sign up to set email alerts
|

Use of insulin pumps and closed‐loop systems among people living with diabetes: A narrative review of clinical and cost‐effectiveness to enable access to technology and meet the needs of payers

Abstract: The use of continuous subcutaneous insulin infusion (CSII) via insulin pumps is today considered standard of care for type 1 diabetes (T1D). Closed-loop systems combining continuous glucose monitoring with automated algorithm-driven insulin delivery have been shown to be safe and efficacious in randomized controlled trials and reallife studies in both paediatric and adult participants with T1D. Implementation of hybrid closed-loop (HCL) systems has shown incremental effectiveness, with further reduction of hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…It should be mentioned that financial considerations and household incomes were not barriers, as access to technology in France is easy, because of the complete reimbursement of AID systems after evaluation of cost-effectiveness by the payers. 17 Although keys of success with the implementation of automated closed-loop insulin delivery have been clearly defined by a position statement, 18 several factors may mitigate the performance of AID technology. CHO counting is perceived as one of the most burdensome tasks by PwT1D and can explain variability in insulin requirements.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that financial considerations and household incomes were not barriers, as access to technology in France is easy, because of the complete reimbursement of AID systems after evaluation of cost-effectiveness by the payers. 17 Although keys of success with the implementation of automated closed-loop insulin delivery have been clearly defined by a position statement, 18 several factors may mitigate the performance of AID technology. CHO counting is perceived as one of the most burdensome tasks by PwT1D and can explain variability in insulin requirements.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence showing beneficial effects of insulin pumps and AID systems in individuals living with type 1 diabetes 14,22 . The use of insulin pumps in people with type 2 diabetes is a more recent practice compared with its use in type 1 diabetes 15 . A meta‐analysis, which included the OPT2MISE study and four smaller randomized studies, has shown the superiority of pump therapy compared with MDI, including a reduction in HbA1c, reduction of daily insulin dose and improved weight maintenance 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to the use of pumps and AID systems for treating type 2 diabetes include the lack of clinical guidelines to select those patients who will benefit from these technologies, lack of FDA approval and CE labelling according to the American and European regulations for AID indications in type 2 diabetes, the variable HHP resources and the varied funding and reimbursement for medical devices and associated HHC services depending on the country. Studies of cost‐effectiveness are now required to show the possible economic advantages of using an AID system in selected people with type 2 diabetes 15 . The availability of HHC services and their reimbursement by the French social insurance is unique and far from being a widespread convenience among other countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations